Inflation without an inflaton - Daniele Bertacca; Raul Jimenez; Sabino Matarrese; Angelo Ricciardone (Physical Review Research, 2025)
We propose a novel scenario in which scalar perturbations, which seed the large-scale structure of the universe, are generated without relying on a scalar field (the inflaton). In this framework, inflation is driven by a de Sitter space time, where tensor metric fluctuations (i.e., gravitational waves) naturally arise from quantum vacuum oscillations, and scalar fluctuations are generated via second-order tensor effects. We compute the power spectrum of such scalar fluctuations and show it to be consistent with near scale invariance. We derive the necessary conditions under which scalar perturbations become significant and much larger than the tensor modes, and we identify a natural mechanism to end inflation via a transition to a radiation-dominated phase. Our proposed mechanism could remove the need for a model-dependent scenario: the choice of a scalar field, as the inflaton, to drive inflation.